Who framed Roger Rabbit? [videorecording (Blu-Ray + DVD)] - Zemeckis, Robert, 1952-; Hoskins, Bob; Lloyd, Christopher, 1938-; Cassidy, Joanna, 1945-; Fleischer, Charles; Kaye, Stubby; Turner, Kathleen, 1954-; Wolf, Gary K. (Touchstone Home Entertainment ; Distributed by Buena Vista Home Entertainment, 2013)
"It's 1947 Hollywood Eddie Valiant ... a down-on-his-luck detective, is hired to find proof that Marvin Acme, gag factory mogul and owner of Toontown, is playing hanky-panky with femme fatale Jessica Rabbit, wife of Maroon Cartoon superstar, Roger Rabbit. When Acme is found murdered, all fingers point to Roger, who begs the Toon-hating Valiant to find the real evildoer"--Container.